A mirrored 5T1C OLED pixel circuit for compensating characteristics variations and voltage drop. (January 2023) - Chu, Hongzhen; Wei, Ning; Yu, Bo; Zhao, Huicheng; Li, Yuehua; Wang, Xinlin; He, Hongyu
Abstract: A pixel circuit with p-type low temperature poly-silicon thin-film transistors (TFTs) is presented for active-matrix organic light-emitting diode displays. This circuit consists of five TFTs and one capacitor. In the circuit, the characteristics, i.e., the threshold voltage and the mobility, are extracted by the mirroring structure, and an adaptive voltage is generated at the gate of the TFT in the programming stage. Therefore, only one capacitor is needed to compensate both the threshold voltage variation and the mobility variation. Meanwhile, in the circuit, the voltage drop of the power line is also compensated. Moreover, the circuit can prevent the image flicker because the organic lighting-emitting diode (OLED) only operates in the emission stage. The circuit simulation results indicate that the OLED current error rates are lower than 4.61% when the threshold voltage variation is ± 0 . 5 V, lower than 6.92% when the mobility variation is ± 30 %, and lower than 3.96% when the voltage drop is − 0 . 5 V .